Bilateral Peripheral Facial Paralysis in a Pregnant Patient Admitted to Emergency Service: A case of Guillain-Barre Syndrome (Annals of Medical Research, 2021)
None
Keywords: Gullian Barre Syndrome; Pregnant; Bilateral Facial Nervous Paralysis.